2016
DOI: 10.1016/j.ijpharm.2016.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Solid lipid nanoparticles co-loaded with doxorubicin and α-tocopherol succinate are effective against drug-resistant cancer cells in monolayer and 3-D spheroid cancer cell models

Abstract: This work aimed to develop solid lipid nanoparticles (SLN) co-loaded with doxorubicin and α-tocopherol succinate (TS) and to evaluate its potential to overcome drug resistance and to increase antitumoral effect in MCF-7/Adr and NCI/Adr cancer cell lines. The SLN were prepared by a hot homogenization method and characterized for size, zeta potential, entrapment efficiency (EE), and drug loading (DL). The cytotoxicity of SLN or penetration was evaluated in MCF-7/Adr and NCI/adr as a monolayer or spheroid cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 32 publications
0
76
0
1
Order By: Relevance
“…94 In this regard, MCTS from MDR cell lines such as breast cancer MCF7/ Adr or ovarian cancer NCI-ADR-RES are useful tools to evaluate innovative solutions to restore DOX cytotoxicity as was shown with intrinsic drug-resistant glioblastoma U87MG cells. 70,71,[95][96][97][98] DOX-loaded nanoplatforms (targeted or nontargeted) that allow the simultaneous administration of several anticancer agents were evaluated in MCTS based on three criteria: accumulation, penetration and cytotoxic effects (Table 2). 70,71,[95][96][97][98] An excellent example of what can be done was the coloading of DOX with the MDR modulator curcumin (CUR) that inhibits different resistance-related pathways.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…94 In this regard, MCTS from MDR cell lines such as breast cancer MCF7/ Adr or ovarian cancer NCI-ADR-RES are useful tools to evaluate innovative solutions to restore DOX cytotoxicity as was shown with intrinsic drug-resistant glioblastoma U87MG cells. 70,71,[95][96][97][98] DOX-loaded nanoplatforms (targeted or nontargeted) that allow the simultaneous administration of several anticancer agents were evaluated in MCTS based on three criteria: accumulation, penetration and cytotoxic effects (Table 2). 70,71,[95][96][97][98] An excellent example of what can be done was the coloading of DOX with the MDR modulator curcumin (CUR) that inhibits different resistance-related pathways.…”
mentioning
confidence: 99%
“…70,71,[95][96][97][98] DOX-loaded nanoplatforms (targeted or nontargeted) that allow the simultaneous administration of several anticancer agents were evaluated in MCTS based on three criteria: accumulation, penetration and cytotoxic effects (Table 2). 70,71,[95][96][97][98] An excellent example of what can be done was the coloading of DOX with the MDR modulator curcumin (CUR) that inhibits different resistance-related pathways. 94,98 Polymeric micelles loaded with DOX and/or CUR (zeta potential of -4.4 mV, 15 nm in size) were decorated with a single-chain fragment variable (scFv), smaller, more stable and less immunogenic than IgG antibody, and were addressed against the GLUT1 protein in overexpressed glioblastoma cells.…”
mentioning
confidence: 99%
“…The combination of TS – an analogue of vitamin E – and DOX loaded into a lipid nanoparticle demonstrated promising in vitro results [16] with modest potential for off target toxicity, therefore forming the foundation of these studies. We developed a novel drug delivery system with in vivo properties that show favorable pharmacodynamics and antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our research group demonstrated that TS improves encapsulation of DOX into lipid nanoparticles [15], with increased cytotoxicity in monolayer and 3-D spheroid models, against MCF-7/Adr and NCI/Adr line cells [16]. Therefore, the aim of this work was to evaluate the in vivo properties of this NLC formulation in an experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…In general, lipid nanoparticles have advantages over other systems used for topical administration: more compatibility with the skin, as lipids are normal components of its structures , enhanced penetration of active compounds in the stratum corneum , low cost, and simple and easy‐to‐scale preparation , excellent physical stability, with no leakage of encapsulated active substances , chemical versatility and biodegradability , controllable release profiles , protection of the encapsulated substance against degradation processes induced by the external medium . …”
Section: Introductionmentioning
confidence: 99%